FLEXIBLE AND MECHANISM MANAGEMENT AFFECTING TEACHERS’ WORKING INCENTIVE IN UNIVERSITY OF QIQIHAR, HEILONGJIANG PROVINCE - Yue, Ge; Pruettikul, Sataporn; Moonmuang, Sukhoom (วารสารวิจัยธรรมศึกษา, 2024)
The research objectives were: 1) To study the component of teachers’ working incentive and flexible and mechanism management in university of Qiqihar, 2) To development the model of flexible and mechanism management factors affecting teachers’ working incentive in university of Qiqihar, And 3) To verify the Model of flexible and Mechanism management factors effecting teachers’ working incentive to fit well with the empirical data. The research design using the quantitative methodology, the population were 2,311 teachers in two public universities of Qiqihar in Heilongjiang Province, The sample size were 396 teachers, determined by G*power program and using stratify random sampling method, the data collecting by a 5 rating scale questionnaires. Divided to 5 sections, There were validity (IOC) of each item between .80-1.0 and reliability on each section between .89-.99, Data analysis by X. SD. CFA and SEM with SPSS and AMOS statistical package program. The research were finding; the teachers’ working incentive divided on the 3 components namely; teachers’ need, teachers’ self-efficacy and teachers’ motivation, and overall was a high level, The model of flexible and mechanism management factors affecting teachers’ working incentive in university of Qiqihar, Heilongjiang province fit well with empirical data (Chi-square =57.387, df =49, CFI=0.999, TLI= 0.998, RMSEA= 0.021), Flexible and mechanism management has positive direct effect on teachers working incentive and Organizational climate with statistically significance at .01, but no significant indirect effect on teachers working incentive.